Learning Outcomes of African Engineering Students in a Chinese Context: A Qualitative Study - Zhu, Jiabin; Yang, Bo; Liu, Niancai (International Journal of African Higher Education, 2018)
China’s ‘One Belt, One Road’ national strategy has brought about both opportunities and challenges to its higher education system and that of neighbouring countries. Increased internationalisation of higher education has resulted in Chinese universities attracting a large number of international students, including those from Africa. However, few studies have been conducted to assess the learning outcomes of African students in a Chinese context. This article provides insight into African engineering students’ self-reported learning outcomes and experiences after studying in China. The fndings reveal that academic and cultural knowledge, cross-cultural communication skills, teamwork skills and changes in personalities and professional vision are common areas of development. The article concludes with recommendations for the design of eﬀective learning experiences. La stratégie nationale chinoise “une ceinture, une route” a généré des opportunités et des défs pour son système d’enseignement supérieur et celui des pays voisins. Avec l’internationalisation croissante de l’enseignement supérieur, les universités chinoises attirent un grand nombre d’étudiants internationaux, y compris des étudiants en provenance d’Afrique. Cependant, peu d’études ont tenté d’évaluer les acquis de l’apprentissage des étudiants africains dans le contexte chinois. Cet article oﬀre un aperçu des acquis autodéclarés des étudiants ingénieurs africains et de leur expérience des études en Chine. Les résultats de ce projet exposent plusieurs domaines communs de développement : les connaissances académiques et culturelles, les compétences de communication interculturelle, la capacité à travailler en équipe et des changements de visions professionnelle et académique. Cet article conclut par des recommandations visant à créer des expériences d’apprentissage efcaces.